EFFECT OF ACCRUALS QUALITY ON EQUITY SECURITY MARKET RETURNS: EVIDENCE FROM THE NAIROBI SECURITIES EXCHANGE - Oluoch, Josephat; Namusonge, Gregory; Onyango, Silas (European Scientific Journal, ESJ, 2015)
This study uses a mixed research design to evaluate the pricing effect of accruals quality among public companies in Kenya. The study’s sample of 39 companies is purposively derived from a population of 60 companies and covers the period January 1993 through December 2013. It relies on secondary data on accruals information from annual financial statements and monthly equity market security prices. Once estimated, accruals quality is further split into its innate and discretionary components. Panel regression of accruals-based portfolio decile premiums on the Fama and French (1993) market pricing factors is used to test the statistical significance of the market excess returns to establish whether and how accruals quality is priced in the Kenyan securities market. The findings show that most of the accruals quality comprises innate accruals quality and that level discretionary accruals quality among listed companies in Kenya is statistically insignificant. They further indicate that there exists accruals quality market return premium at the Nairobi Securities Exchange (NSE) and that the security market returns are inversely related with market returns. In essence, accruals quality is a diversifiable information risk factor at the NSE. Since the conclusions are based on the listed companies in Kenya only, the study recommends that the pricing tests could be conducted on a wider scope of companies that includes non-listed firms since these play a prominent economic role among the developing countries.